Initiating the Digitization of Community Literacy Through GEMATI-POKDES I (Gerakan Jumat Literasi – Pojok Desa Menginspirasi) - Wicaksana, Muhlis; Pardyatmoko; Sukarno; Sari, Nurratri Kurnia (Jurnal Pengabdian Masyarakat Bestari, 2024)
Community service aims to create a Literacy Village at the village level. This community service program is to provide assistance in preparing digital literacy materials for the community in the village through GEMATI-POKDESI (Gerakan Jumat Berliterasi – Pojok Desa Menginspirasi). The purpose of the activity is to provide assistance to cadets in the village environment so that they can develop a culture of community literacy through the management of digitalization of information literacy in the village corner. The method of implementing community service activities is carried out through lectures (socialization of the formation of literacy villages), information editing activities, displaying digital information on the Website. . In addition to being displayed on the Sukoharjo Village website, digital text from Sukoharjo village youth is pasted in the corner of the village. The results of the activities provide social changes in the Sukoharjo Village environment both in the fields of education, lifestyle, and community literacy culture.